Molecular Detection of Leishmania infantum in Naturally Infected Phlebotomus perfiliewi transcaucasicus in Bilesavar District, Northwestern Iran - A Sanei Dehkordi; Y Rassi; MA Oshaghi; MR Abai; S Rafizadeh; MR Yaghoobi-Ershadi; M Mohebali; Z Zarei; F Mohtarami; B Jafarzadeh; A Ranjbarkhah; E Javadian (Tehran University of Medical Sciences, 2011)
Background: Visceral leishmaniasis is caused by Leishmania infantum, transmitted to humans by bites of phlebotomine sand flies and is one of the most important public health problems in Iran. To identify the vector(s), an investigation was carried out in Bilesavar District, one of the important foci of the disease in Ardebil Province in northwestern Iran, during July-September 2008. Methods: Using sticky papers, 2,110 sand flies were collected from indoors (bedroom, guestroom, toilet and stable) and outdoors (wall cracks, crevices and animal burrows) and identified morphologically. Species-specific amplification of promastigotes revealed specific PCR products of L. infantum DNA. Results: Six sand fly species were found in the district, including: Phlebotomus perfiliewi transcaucasicus, P. papatasi, P. tobbi, P. sergenti, Sergentomyia dentata and S. sintoni. Phlebotomus perfiliewi transcaucasicus was the dominant species of the genus Phlebotomus (62.8%). Of 270 female dissected P. perfiliewi transcuacasicus, 4 (1.5%) were found naturally infected with promastigotes. Conclusion: Based on natural infections of P. perfiliewi transcaucasicus with L. infantum and the fact that it was the only species found infected with L. infantum, it seems, this sand fly could be the principal vector of visceral leishmaniasis in the region.